Determination of individual knee-extensor properties from leg extensions and parameter identification. Issue 4 (4th July 2017) - Penasso, H.; Thaller, S.
ABSTRACT: Neural commands control skeletal muscles that act on passive structures and regulate voluntary movements. Mathematical models can simulate such movements and therefore require the knowledge of neuromuscular properties. In contrast to scaling these properties to the individual, we present a non-linear parameter identification method to determine them non-invasively and in vivo . The classic model A describes an excitable contractile element (CE) embedded in a geometrical representation of the leg. Its extension model B is used to study the effects of the force–length relationship and the serial elastic element (SEE). We show the validation of model B and discuss the quality of neuromuscular properties identified from simulations and experiments. The main finding is that identifications that consider CE–SEE dynamics result in increased and more realistic curvatures of the force–velocity relations. This shows that CE and SEE work interdependently and we recommend to co-ordinate the parameter values of muscle–tendon units.